Hidup adalah Perjuangan: Strategi Pemuda Yogyakarta dalam Transisi dari Dunia Pendidikan ke Dunia Kerja - Sutopo, Oki Rahadianto (UI Scholars Hub, 2013)
This article shows the experiences of six young people from Yogyakarta who struggle in the process of school to work transition. These young people creatively implemented long term strategy both inside and outside the field of education They accumulate various kind of capitals so that it can be converted in the future. All of the informants are from middle class background. The result shows they still get benefits from strategies and capital that they had previously created. As a young people from middle class background, they are optimist that they can reach their dream jobs in the future as long as they work hard, creative and struggle hard. The finding of this research supports the qualitative aspect to previous study made by Nilan (2012) Theoretically, it shows the compatibility between concept of long term strategy by Jones (2009), economic, social and cultural capital by Bourdieu (1998) and zigzag journeys by Nilan, Julian, and Germov (2007) as analytical concepts to understand youth transition in Indonesia.